2004
DOI: 10.1242/jeb.00719
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic effects on body mass, energy balance and hypothalamic gene expression in the bank vole

Abstract: We examined the effect of increasing photoperiod, at a constant low temperature, on the body mass and energy budget of the bank vole Clethrionomys glareolus. Simultaneously, we determined the hypothalamic gene expression of neuropeptides and receptors known to be involved in short-term energy balance. Despite an increase in body mass (approximately 10% of initial mass), we found no significant changes in any energetic parameters (food intake, energy assimilation rate, resting metabolic rate and total daily ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
17
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 60 publications
9
17
5
Order By: Relevance
“…However, in spite of substantial increases in SOCS3 gene expression in the ARC of voles exposed to LD, we found no significant changes in the hypothalamic expression of mRNA for NPY, AgRP, POMC and CART genes. Changes in NPY, AgRP, POMC and CART were also not detected in our previous studies, where bank voles (Clethrionomys glareolus) were exposed to SD or LD for 12 weeks (Peacock et al 2004). However, these changes in the first-order neuropeptides believed to control food intake were perhaps not surprising because we have also shown that exposure to LD did not significantly affect food intake, once differences in body mass were accounted for (Peacock et al 2004, Król et al 2005.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, in spite of substantial increases in SOCS3 gene expression in the ARC of voles exposed to LD, we found no significant changes in the hypothalamic expression of mRNA for NPY, AgRP, POMC and CART genes. Changes in NPY, AgRP, POMC and CART were also not detected in our previous studies, where bank voles (Clethrionomys glareolus) were exposed to SD or LD for 12 weeks (Peacock et al 2004). However, these changes in the first-order neuropeptides believed to control food intake were perhaps not surprising because we have also shown that exposure to LD did not significantly affect food intake, once differences in body mass were accounted for (Peacock et al 2004, Król et al 2005.…”
Section: Discussionsupporting
confidence: 53%
“…Changes in NPY, AgRP, POMC and CART were also not detected in our previous studies, where bank voles (Clethrionomys glareolus) were exposed to SD or LD for 12 weeks (Peacock et al 2004). However, these changes in the first-order neuropeptides believed to control food intake were perhaps not surprising because we have also shown that exposure to LD did not significantly affect food intake, once differences in body mass were accounted for (Peacock et al 2004, Król et al 2005. Rather, the increase in mass and adiposity was mediated primarily by an increase in digestive efficiency.…”
Section: Discussioncontrasting
confidence: 43%
“…Similar seasonal changes (i.e. SD-induced decreases in body mass and adiposity) have also been demonstrated in the European hamster (Cricetus cricetus; Canguilhem et al, 1988), montane vole (Microtus montanus; Petterborg, 1978), meadow vole (Microtus pennsylvanicus; Dark and Zucker, 1984), tundra vole (Microtus oeconomus; Wang and Wang, 1996) and bank vole (Clethrionomys glareolus; Peacock et al, 2004).…”
Section: Introductionsupporting
confidence: 63%
“…However, SD had no effect on energy intake in collared lemmings , bank voles (Clethrionomys glareolus) (Peacock et al, 2004) or field voles (Microtus agrestis) after correcting for differences in body mass (Król et al, 2005). In the present study, changing the direction of the photoperiod caused differences in digestible energy intake when juveniles had grown up.…”
Section: The Underlying Mechanism Of Body Mass Regulationcontrasting
confidence: 57%